Formation and Removal Mechanism of Nonmetallic Inclusions in 42CrMo4 Steel during the Steelmaking Process - Tong Qiao; Guoguang Cheng; Yu Huang; Yao Li; Yanling Zhang; Zhanchun Li (Metals, 2022)
Nonmetallic inclusions are harmful to the quality of 42CrMo4 steel. Therefore, the formation and removal mechanism of inclusions in 42CrMo4 steel during the steelmaking process is investigated by industrial trials. The characteristics of inclusions in specimens were analyzed by scanning electron microscopy and energy dispersive spectroscopy. The main type of inclusions in molten steel in the early stage of ladle furnace (LF) refining is MgO-Al2O3 inclusions of irregular shape. CaO begins to appear in MgO-Al2O3 inclusions in the middle and late stages of LF. In the vacuum degassing (VD) refining stage, the inclusions in molten steel completely change into low-melting-point CaO-MgO-Al2O3 inclusions. The existence of [Mg] in molten steel is the fundamental reason for the formation of a large number of MgO-Al2O3 inclusions. Thermodynamic calculation shows that the refractory mainly transfers [Mg] to the liquid steel in the LF refining stage, whereas the slag mainly transfers [Mg] to the liquid steel in the VD refining stage. Kinetic calculation indicates that MgO-Al2O3 inclusions could be removed from molten steel faster than low-melting-point CaO-MgO-Al2O3 inclusions. The fundamental reason for the different removal behavior of the two types of inclusions is that the interfacial tension between the low-melting-point CaO-MgO-Al2O3 inclusions and the liquid steel is 50% lower than that of the MgO-Al2O3 inclusions.